Can Simulated Green Exercise Improve Recovery From Acute Mental Stress? - Wooller, John James; Rogerson, Mike; Barton, Jo; Micklewright, Dominic; Gladwell, Valerie (Frontiers in Psychology, 2018)
This exploratory study enhances previous research into green exercise and addresses a gap in the research by exploring the contribution of individual and combined senses in the recovery of mood and stress after a psychological stressor, whilst rigorously controlling exercise intensity. The hypotheses were: (i) recovery of mood and stress from a state of psychological stress would be greater following simulated green exercise compared to rest, (ii) green exercise would facilitate better recovery than exercise alone and (iii) these effects would remain 10 minutes following intervention. iv) visual stimuli alone would enhance recovery from a state of psychological stress compared to sound. Fifty participants were randomly assigned to one of five groups: REST, exercise, exercise with nature sounds, exercise with nature visual and exercise with nature sound and visual. An initial visit to obtain predicted peak power output values and to familiarize participants with the equipment being used was followed by a second visit, where participants experienced one test condition. Baseline measures of heart rate, blood pressure, total mood disturbance and perceived stress were taken, before participants completed a stressor based on the Trier Social Stress test. Measures of heart rate and blood pressure were recorded in the last 30 seconds of the stressor to assess efficacy of the stressor. Immediately post stressor, measures of mood and perceived stress were taken followed by the intervention assigned (one of five described above). Measures of mood and perceived stress were taken again immediately post intervention and ten minutes post-intervention. Results showed that green exercise improved mood and stress scores more than exercise alone or REST. For both total mood disturbance and perceived stress, improvements in all simulated nature conditions were significantly improved compared to REST or exercise alone immediately post-intervention. There were no significant changes 10 minutes post intervention in either mood or perceived stress compared to immediately post-intervention values in any of the groups. This study suggests that environmental exercise settings including nature sounds, visual or both combined should be considered as important in the use of exercise as a therapeutic activity or recovery from acute psychological stress.